Effect of Pilates on Glucose and Lipids: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Chen, Zehua; Ye, Xiangling; Xia, Yubo; Song, Huiting; Wang, Yi; Guan, Yingxin; Shen, Zhen; Chen, Weijian; Jiang, Tao; Wu, Huai; Xu, Xuemeng (Frontiers in Physiology, 2021)
Objective: The purpose of this study was to examine the effect of Pilates on their levels. Methods: Searches were conducted in five databases to identify the relevant articles published until 29 October, 2020. Paired reviewers independently screened the articles and extracted data from each included study. Meta-analysis was performed to assess the effects of Pilates on blood glucose and lipids. Subgroup analyses and sensitivity analyses were conducted to explore heterogeneity. Results: According to the inclusion and exclusion criteria, fifteen randomized controlled trials (RCTs) comprising 587 participants were included in the study. Overall, Pilates group (PG) had a significantly greater reduction in postprandial blood glucose than the control group (CG) ; glycated hemoglobin (HbA1c); total cholesterol (TC) ; triglycerides(TG) ; and low density lipoprotein cholesterol compared to CG, whereas no significant difference was detected between the two groups in fasting blood glucose, insulin and high density lipoprotein cholesterol (HDL-C). However, by subgroup analysis, we found that compared to the CG, PG showed no significantly improvement in blood glucose and lipids levels for non-diabetics, while it presented a significantly greater decrease in postprandial blood glucose, TC, TG, and LDL-C for diabetic patients. Notably, for diabetic patients, Pilates and medications treatments showed no significant reduction in fasting blood glucose and HbA1c than medications treatment used alone, and Pilates combined with medications and dietary treatments presented no significant improvement in fasting blood glucose than combination of medications and dietary treatments. Conclusions: Overall, Pilates could improve postprandial blood glucose, fasting blood glucose, HbA1c, TG, TC, and LDL-C for diabetic patients, which could be influenced by its duration and intensity. Morever, it had no significant effect on blood glucose and lipids for non-diabetic individuals. However, Pilates, as an adjunctive treatment to medications was not superior to medications used alone in lowering fasting blood glucose and HbA1c. Furthermore, Pilates combined medications and dietary treatments showed no significant improvement in fasting blood glucose, whereas it had a greater reduction in postprandial blood glucose and HbA1c for diabetic patients.